Achieving universal access and moving towards elimination of new HIV infections in Cambodia - Vun, Mean Chhi (International AIDS Society, 2014)
INTRODUCTION: In the mid-1990s, Cambodia faced one of the fastest growing HIV epidemics in Asia. For its achievement in reversing this trend, and achieving universal access to HIV treatment, the country received a United Nations millennium development goal award in 2010. This article reviews Cambodia’s response to HIV over the past two decades and discusses its current efforts towards elimination of new HIV infections. METHODS: A literature review of published and unpublished documents, including programme data and presentations, was conducted. RESULTS AND DISCUSSION: Cambodia classifies its response to one of the most serious HIV epidemics in Asia into three phases. In Phase I (1991–2000), when adult HIV prevalence peaked at 1.7% and incidence exceeded 20,000 cases, a nationwide HIV prevention programme targeted brothel-based sex work. Voluntary confidential counselling and testing and home-based care were introduced, and peer support groups of people living with HIV emerged. Phase II (2001–2011) observed a steady decline in adult prevalence to 0.8% and incidence to 1600 cases by 2011, and was characterized by: expanding antiretroviral treatment (coverage reaching more than 80%) and continuum of care; linking with tuberculosis and maternal and child health services; accelerated prevention among key populations, including entertainment establishment-based sex workers, men having sex with men, transgender persons, and people who inject drugs; engagement of health workers to deliver quality services; and strengthening health service delivery systems. The third phase (2012–2020) aims to attain zero new infections by 2020 through: sharpening responses to key populations at higher risk; maximizing access to community and facility-based testing and retention in prevention and care; and accelerating the transition from vertical approaches to linked/integrated approaches. CONCLUSIONS: Cambodia has tailored its prevention strategy to its own epidemic, established systematic linkages across different services and communities, and achieved nearly universal coverage of HIV services nationwide. Still, the programme must continually (re)prioritize the most effective and efficient interventions, strengthen synergies between programmes, contribute to health system strengthening, and increase domestic funding so that the gains of the previous two decades are sustained, and the goal of zero new infections is reached.